KAJIAN AWAL KELAYAKAN FINANSIAL INVESTASI JALAN REL - Herman . (Jurnal Transportasi, 2016)
Abstract Staging of investment start from the bidding stage to the operational and maintenance stage. Each stage requires a fee to be prepared by the investor. This study aims to calculate the financial feasibility of the implementation of railway passengers. Calculations are based on simulation of the cost of investment, the number of passengers who use it and does not include the risk factors. Results of this study show that the railway project which is not financially feasible requires government support. The government support, such as policies to reduce the burden of the cost of construction and the government guarantee for the hogh uncertain risk could result in the project financial feasibility. Keywords: investment, financial feasibility, government support  Abstrak Tahapan investasi diawali dari tahap penawaran sampai dengan tahap operasional dan pemeliharaan. Setiap tahapan memerlukan biaya yang harus dipersiapkan oleh investor. Penelitian ini bertujuan menghitung kelayakan finansial penyelenggaraan perkeretaapian penumpang. Perhitungan didasarkan simulasi biaya investasi, jumlah penumpang yang menggunakannya dan belum memasukkan faktor risiko. Hasil yang didapat dari penelitian ini adalah bahwa penyelenggaraan perkeretaapian yang tidak layak secara finansial membutuhkan dukungan pemerintah. Bentuk dukungan pemerintah seperti kebijakan untuk mengurangi beban biaya konstruksi dan penjaminan pemerintah untuk risiko ketidakpastian yang terlalu tinggi dapat menghasilkan kelayakan secara finansial. Kata-kata kunci: investasi, kelayakan finansial, dukungan pemerintah